Gender identity and pottery: the size of urns in cremation cemeteries - Krekovič, Eduard (Rei Cretariae Romanae Fautorum Acta, 2015)
It is well known that gender identity can manifest itself in mortuary practices. A couple of years ago I decided to test the hypothesis that men’s, women’s, and children’s urns differ in size. At three Germanic cemeteries in southwestern Slovakia I found that men’s urns tended to be slightly larger than women’s urns, while children’s urns tended to be smaller than men’s or women‘s.